Intrinsic aggregation propensity of the p63 and p73 TI domains correlates with p53R175H interaction and suggests further significance of aggregation events in the p53 family - Kehrloesser, Sebastian (Cell Death Differ, 2016)
The high percentage of p53 missense mutations found in cancer has been attributed to mutant acquired oncogenic gain of functions. Different aspects of these tumour-promoting functions are caused by repression of the transcriptional activity of p53 family members p63 and p73. A subset of frequently occurring p53 mutations results in thermodynamic destabilisation of the DNA-binding domain (DBD) rendering this domain highly unstable. These conformational mutants (such as p53R175H) have been suggested to directly bind to p63 and p73 via a co-aggregation mechanism mediated by their DBDs. Although the DBDs of p63 and p73 are in fact not sufficient for the interaction as shown previously, we demonstrate here that the transactivation inhibitory (TI) domains within the α-isoform-specific C termini of p63 and p73 are essential for binding to p53R175H. Hence, the closed dimeric conformation of inactive TAp63α that renders the TI domain inaccessible prevents efficient interaction. We further show that binding to p53R175H correlates with an intrinsic aggregation propensity of the tetrameric α-isoforms conferred by an openly accessible TI domain again supporting interaction via a co-aggregation mechanism.